Path-Tracking Control of Tilting Quadrotor UAV Based on Variable Structure Sliding Mode Control Method - Qinghua Liu; Ke Zhang; Yunfan Pan; Huan Zhang (International Journal of Aerospace Engineering)
Tilting quadcopter unmanned aerial vehicles have the ability to perform vertical takeoff and landing, hover in the air, and cruise at high speeds, They can complete various flight tasks. Due to the special flight mode of tilting quadcopter unmanned aerial vehicles, in transition mode, as the tilt angle changes, the control process of the drone becomes more complex, and the difficulty of control also increases significantly. This article takes the tilting quadcopter drone as the research object and analyzes its overall layout and flight principles in various flight modes. Analyze using the Newton–Euler method and dynamically model three flight modes. The flight process is controlled using inner and outer loop control methods, and a sliding mode manifold control law for a tilting quadcopter unmanned aerial vehicle is designed using the hyperbolic tangent-sliding mode control method. Finally, MATLAB/Simulink was used to simulate the path-tracking process of the tilting quadcopter unmanned aerial vehicles, proving the stability of the controller.